Organisational change capacity and performance: the moderating effect of coercive pressure - Sukoco, Badri Munir; Supriharyanti, Elisabeth; Sabar, Sabar; Susanto, Ely; Nasution, Reza Ashari; Daryanto, Arief (2022)
Purpose: To examine three dimensions of organisational change capacity (OCC) which have been proposed sequentially in the following order: OCC for change will affect process capacity for change and develop context capacity for change. Specifically, this study explores the moderating effects of coercive pressure. Design/methodology/approach: To test the proposed hypotheses, this study conducted survey among middle-level leaders of the 11 top universities (autonomous higher education institutions – AHEIs) in Indonesia. This study used a sample of 92 respondents, deans 21 and vice deans 71 of 11 top Indonesian universities. To test data processing using the SmartPLS 3.0 tool. Findings: The findings indicate that learning capacity for change is the starting point of OCC, and it influences process capacity and context capacity for change. Coercive pressure strengthens the relationship between learning capacity and context capacity for change. Further, context capacity for change determines organisational performance. Originality/value: This study empirically examines the OCC construction mechanism as follows: learning capacity for change influences process capacity for change and then has an effect on the OCC for change, which ultimately affects organisational performance. © 2021, Emerald Publishing Limited.